ARGE ALP - Eine starke Region trotz oder wegen der Berge? - Chilla, Tobias; Lambracht, Markus (Von der "Revolution der Provinzen" zur Zukunft des Alpenraumes, Festschrift 50 Jahre ARGE ALP 1972-2022, 2022)

Institutional mapping of cross-border cooperation. INTERREG programme analyses with KEEP data - Chilla, Tobias; Lambracht, Markus (European Planning Studies, 2022)
In recent years, a growing number of institutional mapping approaches has reflected on border regions' development. These approaches visualise the relationship between institutional and spatial patterns. In parallel, the quality and quantity of cooperation-related information in the EU KEEP database (DB) is continuously increasing. The aim of our paper is two-fold. Firstly, we aim to understand the cooperation dynamics and funding geographies of the recent INTERREG A period. We do so with the example of cross-border programmes with German participation. More concretely, we scrutinise the relationships that exist between the spatial configurations of funded project cooperation, the involved thematic topics and the role of territorial contexts, particularly in terms of the degree of urbanisation and distance to a border. Secondly, we reflect on the potential and limitations of institutional mapping based on KEEP data. Specifically, we explore the explanatory capacity of institutional mappings based on KEEP data and discuss the blind spots that must be considered and how these could be addressed. The general conclusion from our paper is that institutional mapping based on the KEEP DB proves to be a strong data exploration tool with potential for comparative analyses. However, it has clear limitations with regard to causality testing.
CRIS-Team WoS Importer:2022-04-22

Settlement Systems in Mountain Regions: A Research Gap? - Bertram, Dominik; Lambracht, Markus; Chilla, Tobias (Mountain Research and Development, 2024)
Cities and their networks play a significant role in spatial development. This holds true for settlement systems in general, and there is no reason that this should differ in mountain contexts. However, research on this subject is scarce, and it remains a relatively niche topic. Against this background, our article presents a scoping review of settlement systems in mountain regions, reflecting on thematic foci, temporal developments, and regional differences in the global scientific debate. The results show that the scientific discourse has been a rather Eurocentric debate of modest intensity for several decades. The discussion has become more intense in the past decade because of a substantial number of contributions on Asia. Our findings suggest that the current academic debate does not fully address the potential of settlement systems for sustainable spatial development in mountain areas. Recent articles have been predominantly based on improved data availability and methodological innovation, often in the form of case studies. We conclude that a significant research gap exists in terms of comparative perspectives on settlement systems in mountain regions.
CRIS-Team Scopus Importer:2024-08-23
Keywords: montology; mountain geographies; mountain research; research agenda; scoping review; urbanization

Spatial Development in the European Alps: Topographic Potential Area as a Basic Indicator for Policy Debates - Lambracht, Markus (Papers in Applied Geography, 2023)
The European Alps are characterized by a unique geographical environment. The high altitude and the associated steepness of the slopes pose numerous challenges for spatial development. Furthermore, due to their specific natural characteristics, the Alps constitute a region worthy of preservation, which brings additional considerations in the field of political decision-making. All these facts demand increased political and planning coordination. Debates about spatial development in the Alps, hardly address the regions’ topographic characteristics and their consequences. Based on a Digital Elevation Model (DEM) slope analysis, I argue that topographic factors and their implications for municipalities in the Alpine region have been underestimated in spatial development. In this article, an analytical mapping of the Alpine region based on topographic arguments addresses two research questions: What potentials and limits does slope data reveal for the Alps as a living space? How can this analysis help to identify potentials for spatial development in the Alps? I introduce the Topographic Potential Areas (TPA) and an associated TPA quotient, which relates the potential area based on slope steepness to the total area of the municipal territory. These findings serve as a basis for further analyses to facilitate a sustainable spatial organization of the Alpine region.
CRIS-Team Scopus Importer:2023-10-27
Keywords: Applied geomorphology; feature extraction; GIS; mapping; spatial planning

Städte und Siedlungssystem der Alpen - Chilla, Tobias; Bertram, Dominik; Lambracht, Markus (Geographische Rundschau, 2023)
CRIS-Team Scopus Importer:2023-09-15

The Alpine settlement system: capturing relevance beyond size - Bertram, Dominik; Chilla, Tobias; Lambracht, Markus (Journal of Maps, 2023)
The Alpine settlement system is of key relevance for sustainable development in the mountain region. However, maps on the European scale indicate almost no cities in the Alps but only a few small towns. We argue that a differentiated mapping approach should involve medium and small settlements in mountain regions, as they have a high functional importance for the surrounding area. We present an analytical mapping of the Alpine settlement system based on demographic and accessibility arguments and reflect on two research questions: How to put Alpine towns on the map of spatial development without taking a metropolitan bias? To what extent does this approach help to overcome the ‘size problem’ of the Alpine settlement system? Our ‘new’ map covers the rural area and ‘sees’ small towns, shows the relevance of efficient spatial organisation along valley axes and illustrates the cross-border dimension of towns in spatial proximity to national borders.
CRIS-Team Scopus Importer:2023-01-27
Keywords: Alpine towns; cross-border regional planning‌; rural studies‌; small places‌; sustainable spatial development; territories with geographical specificities